Varāhapurāṇam : vistr̥ta bhūmikā, Hindī anuvāda evaṃ ślokārdhanukramaṇikā sahita - Vyāsa; Jhā, Surakānta; Jhā, Surakānta (Biṭṭhaladāsa Saṃskr̥ta sīrīja ;)
Hindu mythological text, with introduction, Sanskrit text and Hindi translation.